Industrial and organizational psychology in Malaysia - Abdul Rahman, Shukran (Thomson, 2005)
The objective ofthis paper is to introduce the application ofpsychology in workplaces. Specifically this paper addresses the importance fht' profession ofIndustrial and Organizational Psychologist in the increasingly advanced and industrialised Malaysian society. It highlights the areas that the professional cares for, as well as its roles and positions in view of the nation's needs. This paper also describes the historical background of psychology as a field of study and service in Malaysia. Besides justifying the need for Industrial and Organizational Psychology, this paper also discusses essential issues that Industrial and Organizational Psychologists practicing in Malaysia should attend to.